Konsep Kebahagiaan Dalam Tasawuf Menurut Prof. Dr. Muzakkir - Ayu Wandira (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2021)
True happiness can be achieved when humans recognize themselves, recognize their Lord, recognize this world and recognize the hereafter. The peak of human happiness will be obtained when the human being is able to recognize his God. When man recognizes and is close to his Lord, at that moment it seems as if he no longer needs other things because he has been satisfied with his closeness to God. This study aims to determine happiness in Islam, especially happiness in Sufism according to Muzakkir. This type of research is a character study research with a qualitative approach that produces data in the form of arguments about happiness by interviewing the character concerned. The results of this study indicate that happiness in Sufism according to Muzakkir is an effort to live a healthy and happy life, namely (1) Implementing a healthy lifestyle, (2) Halal and good nutrition, (3) Channeling hobbies, (4) Sleeping 7-8 hours per day Charity Ibada, (5) Always be grateful and patient, (6) Don't complain a lot and always think positively.